2017
DOI: 10.1108/gm-03-2016-0036
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the impact of demographic variables on mentoring-managerial effectiveness relationship

Abstract: PurposeThe purpose of this study is to examine the relationship between mentoring, managerial effectiveness and demographic variables. Being in a mentoring relationship offers a low-cost experiential learning, encourages diversity and inclusion, helps in expanding professional associations and boosts engagement. The use of mentoring programs can achieve this to a larger extent by making managers effective. Design/methodology/approachThe study was administered on 350 middle-level managers, representatives of f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 21 publications
(23 reference statements)
1
3
0
Order By: Relevance
“…Second, we used a measure of Type A–B personality specifically designed for the Indian context (Dhar & Jain, 2001). We found that the measure had strong reliability and its use in other studies has demonstrated similarly strong reliability (Madan & Srivastava, 2017). We argue that our measure speaks to the need to utilize measures in organizational psychological and behavioral research (Gelfand et al, 2017) we are conscious that its use may limit the generalizability of our findings to Western contexts.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Second, we used a measure of Type A–B personality specifically designed for the Indian context (Dhar & Jain, 2001). We found that the measure had strong reliability and its use in other studies has demonstrated similarly strong reliability (Madan & Srivastava, 2017). We argue that our measure speaks to the need to utilize measures in organizational psychological and behavioral research (Gelfand et al, 2017) we are conscious that its use may limit the generalizability of our findings to Western contexts.…”
Section: Discussionsupporting
confidence: 68%
“…There is a tradition of using Western developed measures in an Eastern context however this is widely criticized (Gelfand et al, 2017) and researchers have highlighted the need to develop measures that better fit the context (Aycan, 2005). The Dhar and Jain (2001) measure of Type A–B personality is widely used in India and its psychometric properties are considered effective (Madan & Srivastava, 2017). We argue that it is a more valid measure of Type A–B personality given the cultural context of our study and we believe that it has effective application to other Asian contexts with strong collectivist cultures.…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
“…Clearly providing opportunities to strengthen mentors’ abilities to work across social identity differences is critical. While the importance of mentors’ ability to work with mentees of different social identities is well established [ 16 , 38 , 39 , 40 , 41 ], mentors as leaders also need this capacity strengthened. The framework of multi-dimensionality offers mentors support in strengthening their ability to work across dimensions of diversity in social identities, enhancing their capacity to build inclusive workplaces.…”
Section: Frames and Practices To Strengthen Mentorsmentioning
confidence: 99%
“…It is essential for organizations to realize that mentoring, whether formal or informal, could lessen the perceptions of glass ceiling. Madan and Srivastava (2017: 380) propagate that ‘organizations need to make special efforts for providing mentoring opportunities to women and propagate the cross-gender mentoring relationships at various social events in the organization’. The reason being when women managers in higher levels communicate their experiences and viewpoints, this will not only boost other women employee’s diligence and skill development, inspiring them to aspire for higher positions, but will also help establish a support system in place.…”
Section: Managerial Implicationsmentioning
confidence: 99%